PROSEDUR PENCAIRAN DANA SANTUNAN ASURANSI KECELAKAAN TERHADAP KORBAN KECELAKAAN MENINGGAL DUNIA PADA PT.JASA RAHARJA (PERSERO) PURWOKERTO - Reza Aurora Fani; Hardiyanto Wibowo (Review of Applied Accounting Research (RAAR), 2021)
This Final Project is a report on the result of Field Work Practices conducted atPT Jasa Raharja (Persero) Purwokerto. The purpose of this Final Project is to findout, understand and understand the Procedure for Disbursement of AccidentInsurance Compensation Funds for Death Accident Victims at PT. Jasa Raharja(Persero) Purwokerto. Data collection methods use the Observation Method,Documentation Method and Interview Method. From the observations it can beconcluded that the Procedure for Disbursement of Accident InsuranceCompensation Fund Funds for Death Victims at PT. Jasa Raharja (Persero)Purwokerto has been able to apply the elements in the accounting system, namelythe compensation submission form, journal, proof of transactions that can facilitatethe management of the company. PT. Jasa Raharja (Persero) has also implementedseveral elements in an internal control, namely the existence of an organizationalstructure that separates functional responsibilities in a strictmanner and is able toimplement a good accounting system that can be useful forsupervision of companyproperty.